2021
DOI: 10.1007/s10661-021-09640-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the environmental risk and pollution status of soil and water resources in the vicinity of municipal solid waste dumpsites

Abstract: 2400 mg/kg), pH (8.3-8.7), COD (39-1995 mg/ kg), and sulfate levels (17.8-301.6 mg/kg) were altered by the dumpsites. Heavy metal concentrations varied between dumpsites; however, the most commonly prevalent metals across all dumps were Fe (992-41,500 mg/kg), Cr (17.4-139.5 mg/kg), Zn (24.1-177.4 mg/kg), Cu (9.42-148.2 mg/kg), and Mn (25.2-776.5 mg/kg), though recorded concentrations exceeded permissible limits only in certain instances. Evidently, soil samples collected at dumpsites had higher concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The soil heavy metals in mining areas investigated in the research were located in different geographical locations and natural environments, and there were certain differences between studies. Therefore, the random effect model was selected to calculate its effect value [11,12]. This model took into account not only intrastudy variance but also interstudy variance (τ2), which was estimated by maximum likelihood function (REML).…”
Section: Methodsmentioning
confidence: 99%
“…The soil heavy metals in mining areas investigated in the research were located in different geographical locations and natural environments, and there were certain differences between studies. Therefore, the random effect model was selected to calculate its effect value [11,12]. This model took into account not only intrastudy variance but also interstudy variance (τ2), which was estimated by maximum likelihood function (REML).…”
Section: Methodsmentioning
confidence: 99%
“…This tendency can be associated to leaching due to topographic context, with E-W leachates circulation (Bernardo et al 2022a, b, c). Soil pH applies to the concentration of ions (H + ) present in the soil solution, being strongly attracted to negative charges and have capability to replace other cations (Altaf et al 2021;Soubra et al 2021). This parameter control soil adsorption and distribution of heavy metals (Naveed et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, citizens residing in low‐income and rural areas in Lebanon suffer from an elevated burden of disease, because practices such as open dumping and burning constitute the main methods for the treatment and disposal of hazardous and nonhazardous wastes by local administrations, resulting in the contamination of natural resources. A study conducted by Soubra et al (2021) demonstrated that various heavy metals were prevalent in samples collected form dumpsites in southern Lebanon, and many soil parameters were altered, which might have a direct effect on soil fertility, disrupt crop yield, and affect human health. A long‐term strategy for the solid waste sector remains unavailable as low diversion rates continue to be recorded, decentralization efforts remain insufficient, hundreds of open dumpsites have yet to be rehabilitated, a constant reliance of ad hoc emergency strategies persists, and the adoption of a publicly unpopular waste‐to‐energy strategy continues to be touted by the government.…”
Section: Methodological Frameworkmentioning
confidence: 99%